Probing layered arc crust in the Lesser Antilles using receiver functions. Issue 11 (14th November 2018) - Schlaphorst, David; Melekhova, Elena; Kendall, J-Michael; Blundy, Jon; Latchman, Joan L.
Abstract : Oceanic arcs can provide insight into the processes of crustal growth and crustal structure. In this work, changes in crustal thickness and composition along the Lesser Antilles Arc (LAA) are analysed at 10 islands using receiver function (RF) inversions that combine seismological data with vP /vS ratios estimated based on crustal lithology. We collected seismic data from various regional networks to ensure station coverage for every major island in the LAA from Saba in the north to Grenada in the south. RFs show the subsurface response of an incoming signal assuming horizontal layering, where phase conversions highlight discontinuities beneath a station. In most regions of the Earth, the Mohorovičić discontinuity (Moho) is seismically stronger than other crustal discontinuities. However, in the LAA we observe an unusually strong along-arc variation in depth of the strongest discontinuity, which is difficult to explain by variations in crustal thickness. Instead, these results suggest that in layered crust, especially where other discontinuities have a stronger seismic contrast than the Moho, H–k stacking results can be easily misinterpreted. To circumvent this problem, an inversion modelling approach is introduced to investigate the crustal structure in more detail by building a one-dimensional velocity–depth profile for each island. Using this method, it is possible to identify any mid-crustal discontinuity in addition to the Moho. Our results show a mid-crustal discontinuity at about 10–25 km depth along the arc, with slightly deeper values in the north (Montserrat to Saba). In general, the depth of the Moho shows the same pattern with values of around 25 km (Grenada) to 35 km in the north. The results suggest differences in magmatic H2 O content and differentiation history of each island.